A Glimpse Behind the Academic Scenes (KULT_online, 2009)
In a series of 177 short, alphabetically ordered essays, Die akademische Hintertreppe (The Academic Backstairs) by Claus Leggewie and Elke Mühlleitner explains the particulars of academic communication in a humorous vein. The lexicon invites students, young researchers and non-academics alike to participate in the progress of knowledge, with specific highlights on present-day and potential future changes in academic communication.